(untitled) (Al-Mansour Journal, 2022)
The paper tries to explore the grammatical phenomenon of rankshift in Systemic Grammar, a functional grammar that establishes five units or the rank scale , : namely sentence, clause phrase, word and morpheme .Rankshift a Hallidayan term , occurs when a given unit is downgraded or shifted down the rank scale and operates further down its rank or a rank equal to itself as when a clause which has to operate in sentence structure operates at q “ qualifier” in a nominal group. The paper , quite significantly, introduces the systemic background that enunciates the systemic theory whose organising concept system rather than structure. The paper then, grammatically explores rankshifted elements, successive rankshifting, degrees of rankshifting and types of rankshift .It ends with some concluding manifestations that serve to highlight the importance and necessity of this downgraded process.